POLA RESPON MAHASISWA IAIN SALATIGA TERHADAP INFORMATION AND COMMUNICATION TECHNOLOGIES (ICT) - Winarno Winarno (ATTARBIYAH: Journal of Islamic Culture and Education, 2016)
Information and communication technology that is now developing to give effect to the learning process. There is a change in the learning process, which is usually done limited learning in the classroom with a predetermined schedule developed into a distance learning can be done anywhere and anytime. Lessons usually involve facilities in the form of material like a book but now growing by utilizing the network (network) by using a computer with internet technology, thus forming pembelajaraan "online". Learning with the charge of information technology will be effective if the teacher's role is as a facilitator in the learning or learning that makes it easy for learners to learn is no longer as informants. The Research method used quantitative descriptive, sampling techniques using purposive sampling technique with 116 students in the sample. The results showed: opinions about the presence of hotspots IAIN Salatiga in which they were pleasant. The existence of free internet area in the library was requested to be increased. As the concluding opinion, most respondents responded “mediocre” or “less satisfied” with the ICT service in IAIN Salatiga.